PENERAPAN METODE PEMBELAJARAN GUIDE NOTE TAKING (GNT) UNTUK MATERI SPLDV PADA KELAS VIII SMP - Maria Anita Sero; Juwita Merdja; Ariswan Usman Aje (Program Studi Pendidikan Matematika, 2020)
This study aims to determine (1) Guide Note Taking (GNT) learning tools on a two-variable linear equation system in class VIII students of SMPK Swadaya Maukaro in the 2018/2019. (2) Learning outcomes through learning Guide Note strategies Taking (GNT) material on the two-variable linear equation system for class VIII SMPK Swadaya Maukaro in the 2018/2019. This type of research used in this research is experimental research with the approach used is a quantitative approach. The subjects in this study were 20 students of class VIII SMPK Swadaya Maukaro. The research result states that the results of the preparation of the Guide Note Taking learning tool for the two-variable linear equation system material produce a good learning tool because it meets the requirements based on validity, reliability, and sensitivity. Results of covariance data analysis obtained f-count = 5.241> f table = 4.45 or it can be seen that with dk numerator 1 and dk denominator 19, giving a significant value, then this shows that learning guide note taking is considered to be able to improve learning outcomes for the material of two-variable linear equation systems in class VIII students of SMPK Swadaya Maukaro.